THE IMPACT OF WATER COLLECTION AS A TASK ON WOMEN IN DRIVING SUSTAINABLE FUTURE FOR HUMANITY IN NIGERIA - Nwobi, Uchechukwu Anthony; Nwagbara, Fidelis C.; Eze, Chima Fidelis (African Journal of Social and Behavioural Sciences, 2022)
Performing the task of water collection by women for household use has increased drastically and constituted great challenges to them despite the target set by sustainable development goal to provide access to sustainable water, basic sanitation and hygiene in order to redress the challenges among the vulnerable groups, those in low and middle income countries. It is the foregoing scenarios that precipitated the innate desire to draw the following objectives of the study. Specifically, the study will ascertain, investigate and find out the extent to which water collection as a task has affected pregnant women in Nigeria, subjected women to waterborne diseases and denied women the opportunity of earning a decent living respectively. The paper is an ex-post facto research and adopted its analytical methodology from conventional content analysis based on secondary data gleaned from journals, textbooks, newspapers, web pages and government publications. Meanwhile, the study employed feminist theory as the theoretical umbrella for this discourse. The study revealed that it was a significant burden on women to fetch water while pregnant. Several women and their kids contracted water borne diseases and because they do not have a decent living. The paper recommends among other things the proper implementation of the national task shifting policy of the federal government. Women should be empowered in skill training and education in order to make them have a decent living.